PERLINDUNGAN HUKUM TERHADAP ANAK DI BAWAH UMUR DALAM PENYALAHGUNAAN NARKOTIKA - Tamata, Braja Larkov; Setiawan, Puguh Aji; Hartana, Hartana (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study examines legal protection for minors involved in narcotics abuse. Children who engage in narcotics abuse are supposed to receive legal protection by Law Number 11 of 2012 concerning the Juvenile Criminal Justice System; however, in practice, criminal sanctions are still imposed based on Law Number 35 of 2009 concerning Narcotics. The research employs a normative juridical method with descriptive-prescriptive analysis. The findings indicate that the factors causing children to abuse narcotics include internal factors (such as an inability to adapt socially) and external factors (such as family environmental conditions). Analysis of Decision Number 1556/Pen.Pid/2021/PN.Jkt.Utr reveals that the court has not fully implemented the child’s best interests principle within the juvenile justice system.